2022
DOI: 10.1302/0301-620x.104b2.bjj-2021-1180.r1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a novel classification system to predict local recurrence in sarcoma patients undergoing hemipelvectomy with iliosacral resection

Abstract: Aims Iliosacral sarcoma resections have been shown to have high rates of local recurrence (LR) and poor overall survival. There is also no universal classification for the resection of pelvic sarcomas invading the sacrum. This study proposes a novel classification system and analyzes the survival and risk of recurrence, when using this system. Methods This is a retrospective analysis of 151 patients (with median follow-up in survivors of 44 months (interquartile range 12 to 77)) who underwent hemipelvectomy wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…According to Feiz-Erfan et al, the extent of resection (subtotal/total) in metastases does not influence overall survival, although there is a trend towards en bloc resection with regard to better local control [22]. Gosheger et al, however, found a significant difference in the extent of resection in patients with sacral/pelvic sarcoma [57].…”
Section: Survival Analysismentioning
confidence: 99%
“…According to Feiz-Erfan et al, the extent of resection (subtotal/total) in metastases does not influence overall survival, although there is a trend towards en bloc resection with regard to better local control [22]. Gosheger et al, however, found a significant difference in the extent of resection in patients with sacral/pelvic sarcoma [57].…”
Section: Survival Analysismentioning
confidence: 99%
“…Due to its unique location and small numbers of patients presenting annually to each unit, a classification for the resection of iliac tumours which invade the sacrum has been lacking, a situation which this study from Münster (Germany) sought to remedy. 5 The team carried out a retrospective analysis of 151 patients who under-…”
Section: Predict Local Recurrence In Sarcoma Patients Undergoing Hemi...mentioning
confidence: 99%
“…Due to its unique location and small numbers of patients presenting annually to each unit, a classification for the resection of iliac tumours which invade the sacrum has been lacking, a situation which this study from Münster (Germany) sought to remedy. 5 The team carried out a retrospective analysis of 151 patients who underwent hemipelvectomy for the above diagnosis at a single specialist centre. Having reviewed the series, they went on to devise a six-category classification based on the relationship between the resection and the sacroiliac joints, neuroforamina, and midline.…”
Section: Predict Local Recurrence In Sarcoma Patients Undergoing Hemi...mentioning
confidence: 99%
“…This balance is difficult to achieve with tumours that require resection of the sacroiliac joint (SIJ), as these are associated with both higher rates of recurrence and poor functional outcomes. 1,2 Despite the associated perioperative morbidity and mortality, resection of locally advanced iliosacral tumours offers the potential for a cure and long-term survival. 3,4 Modern multidisciplinary approaches and classification systems for sacropelvic tumours have brought some clarity to the surgical planning process and expected functional outcomes of patients undergoing iliosacral resection.…”
Section: Introductionmentioning
confidence: 99%
“…This balance is difficult to achieve with tumours that require resection of the sacroiliac joint (SIJ), as these are associated with both higher rates of recurrence and poor functional outcomes. 1,2 Despite the associated perioperative morbidity and mortality, resection of locally advanced iliosacral tumours offers the potential for a cure and long-term survival. 3,4…”
Section: Introductionmentioning
confidence: 99%